Ex-vivo anti-inflammatory potential of naturally occurring molecules bixin, purpurin and psoralen - SREENIVASA REDDY S; KRISHNA K.L; SUBBA RAO M.V.S.S.T. (International Journal of Pharma and Bio Sciences, 2017)
The present research was accomplished to evaluate the ex-vivo anti-inflammatory potential of natural compounds- bixin, purpurin and psoralen by albumin denaturation assay, membrane stabilization assay at different concentrations. Diclofenac sodium was used as standard reference. In human red blood cell (HRBC) membrane stabilization assay, psoralen 57.01±0.65%, bixin 40.78±0.75%, purpurin 28.94±0.57% showed activity at 1 mM. In protein denaturation assay, psoralen 49.49±0.19%, bixin 38.70±1.05% and purpurin 30.51±0.56% showed activity at 1 mM. But the ability of test drugs to protect the erythrocyte membrane lysis and protein from denaturation was clearly seen at 2 mM when compared to diclofenac-sodium which showed highest effect 78.14±0.67% at 1 mM concentration in HRBC membrane lysis assay and 81.79±0.53% at 1 mM concentration in protein denaturation assay. In HRBC membrane assay, Psoralen 99.5±0.46%, bixin 77.37±2.18% and purpurin 60.83±0.75% showed significant activity at 2 mM. Psoralen showed the lowest IC50 value i.e. 475.76±0.98 mM whereas standard drug diclofenac sodium IC50 value was 320.67±0.60 mM. In protein denaturation assay Psoralen 96.23±0.29%, bixin 78.57±0.53%and purpurin 63.66±0.10% showed significant activity at 2 mM. Psoralen showed the lowest IC50 value i.e. 507.61±1.26 mM whereas standard drug diclofenac sodium IC50 value was 305.81±0.78 mM. The selected test drugs inhibited shrinkage of the cells as well as the series of actions, which activate or increase the release of this intracellular portion. However, test drugs significantly inhibited the lysis of erythrocytes. In addition, test drugs also were effective in preventing heat induced protein denaturation when compared to standard drug diclofenac sodium IC50.